2024
DOI: 10.3390/foods13010163
|View full text |Cite
|
Sign up to set email alerts
|

AFB1 Triggers Lipid Metabolism Disorders through the PI3K/Akt Pathway and Mediates Apoptosis Leading to Hepatotoxicity

Tiancai Wang,
Xiabing Li,
Guangqin Liao
et al.

Abstract: As the most prevalent mycotoxin in agricultural products, aflatoxin B1 not only causes significant economic losses but also poses a substantial threat to human and animal health. AFB1 has been shown to increase the risk of hepatocellular carcinoma (HCC) but the underlying mechanism is not thoroughly researched. Here, we explored the toxicity mechanism of AFB1 on human hepatocytes following low-dose exposure based on transcriptomics and lipidomics. Apoptosis-related pathways were significantly upregulated after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Moreover, AFB1 alters lipid metabolism, which reduces the body's growth performance by limiting lipogenesis and promoting lipolysis [31]. The specific mechanism may be that AFB1 can lead to dysregulation of fat metabolism by affecting the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (AKT) signaling pathway [32]. For the F/G, it has been demonstrated that AFB1 causes damage to the intestinal barrier and reduces the activity of pancreatic enzymes, amylase, and trypsin, affecting the efficiency of food absorption [33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AFB1 alters lipid metabolism, which reduces the body's growth performance by limiting lipogenesis and promoting lipolysis [31]. The specific mechanism may be that AFB1 can lead to dysregulation of fat metabolism by affecting the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (AKT) signaling pathway [32]. For the F/G, it has been demonstrated that AFB1 causes damage to the intestinal barrier and reduces the activity of pancreatic enzymes, amylase, and trypsin, affecting the efficiency of food absorption [33].…”
Section: Discussionmentioning
confidence: 99%